2020
DOI: 10.3390/nu12103058
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Roles of Casein-Derived Peptides by Regulation of Trans-Intestinal Cholesterol Excretion and Bile Acid Synthesis

Abstract: Hyperlipidemia, a syndrome characterized by an abnormal elevation of blood lipids, causes chronic lethal metabolic disorders. Although statins are regularly prescribed to patients, an alternative to treat the burden of excessive lipids is required for cholesterol control. In this study, it was found that the treatment of casein hydrolyzed by pepsin and trypsin induced trans-intestinal cholesterol excretion (TICE) through ATP-binding cassette subfamily G members 5 (ABCG5) expression. Next, we analyzed sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Consequently, we discovered 11 peptide sequences in fraction #2 ( Table 2 ). To prove the effects of these 11 synthetic peptides for ABCG5 and ABCG8 regulation, we performed analysis by using 1 μg/mL in distilled water of each peptide to treat Caco-2 cells [ 20 , 33 ]. We confirmed that peptides 1 and 8 significantly upregulated ABCG5 and ABCG8 expression by 1.5-fold ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, we discovered 11 peptide sequences in fraction #2 ( Table 2 ). To prove the effects of these 11 synthetic peptides for ABCG5 and ABCG8 regulation, we performed analysis by using 1 μg/mL in distilled water of each peptide to treat Caco-2 cells [ 20 , 33 ]. We confirmed that peptides 1 and 8 significantly upregulated ABCG5 and ABCG8 expression by 1.5-fold ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous studies, TICE steadily decreased upon movement toward the distal intestine and peptide-derived TICE increased only in the proximal intestine. Therefore, peptide-mediated ABCG5 and ABCG8 upregulation effectively increased fecal cholesterol excretion [ 10 , 20 ]. Our in vivo results showed that peptide 1 and 8 downregulated the serum cholesterol levels while increasing the fecal cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations